Proceedings of the VI National Meeting of the Italian Group of Paleopathology (GIPaleo) - VV., AA. (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2022)
18 giugno 2021 Apertura lavori Ore 14:30 I Sessione Ore 15:15 II Sessione Ore 17:10 19 giugno 2021 III Sessione Ore 9:00 IV Sessione Ore 10:55 Sessione Poster Ore 14:30 V Sessione Ore 15:35 VI Sessione Ore 17:30 Chlusura lavori Ore 18:45 [read more]